(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
Existential philosopher Robert Romanyshyn is determined to understand the modern subject’s felt-sense of alienation. This paper contributes to his effort by putting his notion of the technological worldview into conversation with the concept of the half-connecting body. Feelings of alienation are supported by an identifiable body practice in everyday life.